Nonobstetric Abdominal Surgery During Pregnancy and Birth Outcomes: A Danish Registry-based Cohort Study. Issue 1 (24th March 2021) - Rasmussen, A.S.; Christiansen, C.F.; Ulrichsen, S.P.; Uldbjerg, N.; Nørgaard, M.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:469–476) When considering nonobstetric abdominal surgery during pregnancy, a balance must be found between the need for the procedure and maternal and fetal safety. A number of previous studies have helped define the risk of adverse birth outcomes in this setting. This study aims to add to the existing body of literature by examining the association between nonobstetric abdominal surgery and small-for-gestational-age (SGA) neonatal status, preterm birth, and miscarriage outcomes.